Role of zinc in insulin regulation and diabetes - Poudel, Resham Raj; Bhusal, Yuvaraj; Tharu, Biswaraj; Kafle, Nisha Kusum (Journal of Social Health and Diabetes, 2017)
Zinc (Zn) affects glucose metabolism through insulin regulation and has potential implication in diabetes. Zn deficiency has not been proven in diabetes; however, observations of hyperzincuria, hypozincemia, and Zn malabsorption in diabetes indicate additional requirements for Zn. Mutation in Zn transporter 8 – a key protein in insulin secretion – has been associated with Type 2 diabetes. Zn supplementation in prediabetics and diabetics has been supported to improve plasma glucose, hemoglobin A1c (HbA1c), and lipids and potentially improve insulin sensitivity, reduce oxidative stress, and protect from renal damage.
Keywords: Diabetes; hyperzincuria; hypozincemia; insulin; zinc